Measuring specific mental illness diagnoses with functional impairment : workshop summary / Jeanne C. Rivard and Krisztina Marton, rapporteurs ; Committee on National Statistics and Board on Behavioral, Cognitive, and Sensory Sciences, Division of Behavioral and Social Sciences and Education and Board on Health Sciences Policy, Institute of Medicine ; National Academies of Sciences, Engineering, and Medicine. - Rivard, Jeanne Catherine (The National Academies Press, 2016)
The workshop summarized in this report was organized as part of a study sponsored by the Substance Abuse and Mental Health Services Administration (SAMHSA) and the Office of the Assistant Secretary for Planning and Evaluation of the U.S. Department of Health and Human Services, with the goal of assisting SAMHSA in its responsibilities of expanding the collection of behavioral health data in several areas. The workshop brought together experts in mental health, psychiatric epidemiology and survey methods to facilitate discussion of the most suitable measures and mechanisms for producing estimates of specific mental illness diagnoses with functional impairment. The report discusses existing measures and data on mental disorders and functional impairment, challenges associated with collecting these data in large-scale population-based studies, as well as study design and estimation options.
Keywords: Mental illness -- Diagnosis.